The Aesthetics of Color and Its Significance in the Poems of Yusuf Al-Sayigh - الغانمي, أماني حارث مالك; الزبيدي, إحسان ناصر حسين (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Undoubtedly, the arts, in their various verbal and auditory forms, are expressive patterns through which humans shape their human experiences and present their perceptions of themselves and the world they live in. Poetry, as a verbal art with a descriptive nature, is the creative poet's endeavor to shape an alternative parallel world to the real world, where their dreams, hopes, and aspirations are realized. They achieve this by transforming the visual reality into a visual verbal text. It is from here that the journey of uncovering the close artistic relationship between words and colors began, and expressing the semantic and aesthetic functions of colors - with their emotional qualities - in the poems of Yusuf Al-Sigh, which are rich in imagery, colors, shades, and lines. Images are the pillar of expression for this poet and his effective means of stimulating the imagination of the recipient.